ANALISIS PENGELOLAAN ADMINISTRASI KEUANGAN PADA KANTOR PENGADILAN AGAMA GUNUNGSITOLI - RAHMIAH MENDROFA; MARIA MAGDALENA BATE’E; YAKIN NIAT TELAUMBANUA (LP2MTBM MAKARIOZ, 2022)
This study aims to determine the financial administration management at the Gunungsitoli Religious Court 2021. The type of research used in this research is a qualitative descriptive approach. The data processed is a summary of the budget of the Gunungsitoli Religious Court Office which is obtained from the annual report of the Gunungsitoli Religious Court Office. The analytical technique used in this research is descriptive analysis technique, namely by collecting and filtering the information obtained thoroughly and in detail, then described in order to obtain a clear picture. Based on the results of data collection at the Gunungsitoli Religious Court Office, it can be concluded that the Management of Financial Administration at the Gunungsitoli Religious Court Office is in accordance with the Law of the Republic of Indonesia Number 1 of 2004 concerning State Treasury Article 55 of Law of the Republic of Indonesia Number 17 of 2003 concerning State Finances and Law No. - Law Number 12 of 2018 concerning Budget Revenue and Expenditure December 31, 2021, PP 71 of 2010 concerning Government Accounting Standards and principles of sound financial management in government, as well as Regulation of the Minister of Finance Number: 222/PB/2016 concerning Guidelines for Compilation and submission of reports accrual-based finance at the ministries/agencies, but not yet optimal because the realization has not yet reached 100%, which is 94.64%.